Actividad física y estado nutricional en adultos mayores de la parroquia San Pedro de Vilcabamba - Herrera Macas, Richard Andrés (2022)
Physical activity and an adequate nutritional state are fundamental pillars in the preservation of health and quality of life in older adults. The aim of this study was to evaluate the level of physical activity and nutritional state according to age and sex, and to establish the relationship between these two variables, among older adults in the parish of San Pedro de Vilcabamba. A quantitative, descriptive, observational, cross-sectional and correlational approach was used, implementing a guided interview, where the sample consisted of older adults from the parish of San Pedro de Vilcabamba in the city of Loja, 77 of whom met the inclusion criteria, with a predominance of 57.2% (n=44) being female. The International Physical Activity Questionnaire - Elderly (IPAQ-E) was applied to evaluate the level of physical activity; 67.5% (n=52) presented a high level, of which 20.8% (n=16) corresponded to women aged 65 to 74 years and 18.2% (n=14) to men aged 75 to 84 years. The Mini Nutritional Assessment (MNA) was used to assess nutritional state; 61% (n=47) of the participants showed a normal nutritional state, of which 18.2% (n=14) corresponded to females aged 65-74 years, followed by 16.9% (n=13) belonging to males of the same age range. Older adults in the parish of San Pedro de Vilcabamba had a high level of physical activity and a normal nutritional state, and a statistically significant relationship was found between these variables